2017
DOI: 10.1038/srep45667
|View full text |Cite
|
Sign up to set email alerts
|

Transition between strong and weak topological insulator in ZrTe5 and HfTe5

Abstract: ZrTe5 and HfTe5 have attracted increasingly attention recently since the theoretical prediction of being topological insulators (TIs). However, subsequent works show many contradictions about their topolog-ical nature. Three possible phases, i.e. strong TI, weak TI, and Dirac semi-metal, have been observed in different experiments until now. Essentially whether ZrTe5 or HfTe5 has a band gap or not is still a question. Here, we present detailed first-principles calculations on the electronic and topological pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 35 publications
15
93
0
Order By: Relevance
“…Hall effect data shows electron-like carriers at low temperature [16], implying some of these additional bands must be populated and Dirac-like or massive Dirac-like features should be present. Note that these features are extremely sensitive to cell volume and strain [17], which may explain the conflicting experimental reports on the electronic properties and topological signatures in ZrTe 5 [4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Hall effect data shows electron-like carriers at low temperature [16], implying some of these additional bands must be populated and Dirac-like or massive Dirac-like features should be present. Note that these features are extremely sensitive to cell volume and strain [17], which may explain the conflicting experimental reports on the electronic properties and topological signatures in ZrTe 5 [4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 97%
“…This anomaly is strongly sample dependent, ranging in its position from ∼ 10K to 150K. Recently, it has been suggested that the topological nature of the band structure and associated transport properties of ZrTe 5 depend strongly on the growth technique [17]. Nevertheless, the complicated history of this material highlights the need for robust low-energy signatures of Dirac-like band structures.…”
mentioning
confidence: 99%
“…It has attracted substantial interest lately in the wave of Dirac and topological material exploration [2], due to the theoretical prediction of a large-gap quantum spin Hall insulator phase in its monolayer form [3]. Theory also predicts that the electronic structure of bulk ZrTe 5 resides near the phase boundary between weak and strong topological insulators (TIs) [3,4], providing an ideal platform for studying topological phase transitions. Surface-sensitive spectroscopy techniques such as angle-resolved photoemission spectroscopy (ARPES) and scanning tunneling spectroscopy have recently been used to probe the surface and bulk states of ZrTe 5 [5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…This conclusion should also apply to other MX 2 /h-BN vdWHs. [76,77] The study of a vdWH of MX 2 based on other 2D insulators is of great interest and a new opportunity to improve the performance of TMD-based optoelectronic devices. [53] Copyright 2015, Macmillan Publishers Limited.…”
Section: Figurementioning
confidence: 99%
“…b) Band alignment of the MoS 2 /graphene vdWH at equilibrium state. [141,160] In addition, a WS 2 / Bi 2 Te 3 photodetector with wide photoresponse range from 370 to 1550 nm and short response time of ≈20 ms has been demonstrated by Fan et al [76] Its photoresponsivity and detectivity were measured up to 30.7 A W −1 and 2.3 × 10 11 cm Hz 1/2 W −1 , respectively. c) Band alignment and working mechanism of the MoS 2 /graphene vdWH.…”
Section: Photodetectorsmentioning
confidence: 99%